Extranodal NK/T-Cell Lymphoma With Widespread Cutaneous and Subcutaneous Involvement on 18F-FDG PET/CT. (27th October 2022) - Filizoglu, Nuh; Ozguven, Salih; Ones, Tunc; Turoglu, Halil Turgut; Erdil, Tanju Yusuf
Abstract: Nasal-type extranodal natural killer/T-cell lymphoma is an aggressive rare type of lymphoma that mostly affects the nasal cavity and adjacent areas. However, some patients can present with distant nodal or extranodal involvement including the Waldeyer ring, gastrointestinal tract, genitourinary organs, lung, thyroid, skin, or adrenal glands. Herein, we present a unique case of extranodal natural killer/T-cell lymphoma with widespread cutaneous and subcutaneous involvement on 18 F-FDG PET/CT.